Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s11105-014-0730-4
|View full text |Cite
|
Sign up to set email alerts
|

Remnants of the Legume Ancestral Genome Preserved in Gene-Rich Regions: Insights from Lupinus angustifolius Physical, Genetic, and Comparative Mapping

Abstract: The narrow-leafed lupin (Lupinus angustifolius) was recently considered as a legume reference species. Genetic resources have been developed, including a draft genome sequence, linkage maps, nuclear DNA libraries, and cytogenetic chromosome-specific landmarks. Here, we used a complex approach, involving DNA fingerprinting, sequencing, genetic mapping, and molecular cytogenetics, to localize and analyze L. angustifolius gene-rich regions (GRRs). A L. angustifolius genomic bacterial artificial chromosome (BAC) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 75 publications
5
28
1
Order By: Relevance
“…Nevertheless, deciphering the molecular background underlying the Ku locus took more than decade of extensive research involving various techniques, from BAC library screening via DNA hybridization, restriction siteassociated physical and linkage mapping, fluorescent in situ hybridization of DNA probes in metaphase chromosomes, Sanger, 454 and Hi-seq sequencing to gene expression profiling (Książkiewicz et al 2016;Nelson et al 2017Nelson et al , 2006. Although a similar BAC library approach was applied to L. angustifolius Phomopsis stem blight resistance markers PhtjM2 (linked with PhtjR) and Ph258M2 (Phr1), it did not yield resistance gene identification or the development of tightly linked diagnostic markers (Książkiewicz et al 2013(Książkiewicz et al , 2015. Those studies showed convincingly that MFLP-derived probes are not suitable for positional cloning of particular genes because they hybridize to numerous loci dispersed in the genome, localized both in repetitive and gene-rich regions.…”
Section: Tools For Marker-assisted Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, deciphering the molecular background underlying the Ku locus took more than decade of extensive research involving various techniques, from BAC library screening via DNA hybridization, restriction siteassociated physical and linkage mapping, fluorescent in situ hybridization of DNA probes in metaphase chromosomes, Sanger, 454 and Hi-seq sequencing to gene expression profiling (Książkiewicz et al 2016;Nelson et al 2017Nelson et al , 2006. Although a similar BAC library approach was applied to L. angustifolius Phomopsis stem blight resistance markers PhtjM2 (linked with PhtjR) and Ph258M2 (Phr1), it did not yield resistance gene identification or the development of tightly linked diagnostic markers (Książkiewicz et al 2013(Książkiewicz et al , 2015. Those studies showed convincingly that MFLP-derived probes are not suitable for positional cloning of particular genes because they hybridize to numerous loci dispersed in the genome, localized both in repetitive and gene-rich regions.…”
Section: Tools For Marker-assisted Selectionmentioning
confidence: 99%
“…Highdensity linkage maps carrying thousands of markers, including gene-based sequence tagged sites (STS), were constructed and aligned to the draft genome sequence (Hane et al 2017;Kamphuis et al 2015;Nelson et al 2006;Yang et al 2013b). Exploitation of BAC resources for cytogenetic mapping resulted in the integration of all linkage groups with the corresponding chromosomes, as well as in the identification of several gene-rich regions (Książkiewicz et al 2013(Książkiewicz et al , 2015Leśniewska et al 2011;Przysiecka et al 2015;Wyrwa et al 2016). The release of reference transcriptomes for wild and domesticated lupin accessions constituted a platform for targeting particular genes of interest (Kamphuis et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Of all the known species of genistoid legume (> 2400; Cardoso et al ., ), it has the most advanced set of genomic resources including a comprehensive transcriptome‐based unigene assembly, two genome survey sequences, two large insert genomic libraries and extensive collections of wild and domesticated germplasm (Kasprzak et al ., ; Gao et al ., ; Berger et al ., ; Yang et al ., ; Cannon et al ., ; Kamphuis et al ., ; Smýkal et al ., ). Gene‐rich regions of L. angustifolius revealed well‐conserved microsyntenic links to five reference legume species, which facilitated gene annotation by sequence similarity (Książkiewicz et al ., , ). It is therefore a highly suitable model system for investigating the FT clade in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…During the early divergence of some downstream lineages, dated to roughly~30-55 mya, additional independent WGD events probably occurred, affecting Mimosoideae-Cassiinae-Caesalpinieae, Detarieae, Cercideae, and Lupinus clades [75]. Large-scale duplication and/or triplication in the L. angustifolius genome has been well-evidenced by recent studies involving linkage and comparative mapping [17,36] and microsynteny analysis of selected gene families [30,31,34,62,63]. These WGD events apparently contributed to multiplication of the gene copy number of L. angustifolius GS and PEPC genes because hypothetical duplicates were found in sister branches of the phylogenetic tree and the genome regions harboring these genes shared common collinearity links.…”
Section: The Major Events Promoting the Evolution Of Gs And Pepc Genementioning
confidence: 97%
“…Selected BAC clones have been used as anchors for the integration of linkage groups in particular chromosomes by the molecular cytogenetic approach [30,31] and have served as material in evolutionary studies of the Lupinus genus [32,33]. Strong microsynteny in gene-rich regions between narrow-leafed lupin and other model legumes has also been observed [17,19,20,34,35]. Moreover, new evidence of widespread triplication within the L. angustifolius genome, possibly arising from a polyploidization event, has been found [11].…”
Section: Introductionmentioning
confidence: 99%